Richardson Cascadic Multigrid Method for 2D Poisson Equation Based on a Fourth Order Compact Scheme - Li Ming; Li Chen-Liang (Journal of Applied Mathematics)
Based on a fourth order compact difference scheme, a Richardson cascadic multigrid (RCMG) method for 2D Poisson equation is proposed, in which the an initial value on the each grid level is given by the Richardson extrapolation technique (Wang and Zhang (2009)) and a cubic interpolation operator. The numerical experiments show that the new method is of higher accuracy and less computation time.